Perancangan Indoor Modular Booth Display untuk Produk Fashion - Filbert, Kevin Hartanto (Intra, 2017)
The growth of shopping center in Surabaya makes the business begin to innovate in creating business opportunities. Currently emerging markets that only last for 3 days to accommodate the businessmen, both new and old. So there are problems display booth display design, selection of materials and construction systems appropriate to answer the needs of displays that have many functions (multifunction), which accommodates the needs of display clothes, shoes, bags, accessories and easily dismantled pairs (knockdown). In addition to marketing its products, this market activity became one of the alternatives to promote the brand they bring, to be known by the public.The method used in the design starts from the stage of empathize and define the data collection with direct observation and interviews, both to the tenant and the organizers of pop-up market. After the data collection phase, the existing data is analyzed. Then proceed to the ideate stage, through the brainstorming process of ideas, solve problems, and determine the values of the design. After the ideate stage go to the prototype stage, where the process of visualizing ideas to get the desired result up to the manufacturing stage is realized in the form of prototype with a scale of 1: 1. After the prototype finished, a test is done to get feedback from users and refined through Implement stage to improve the product.Â The result of this design is that the product has been oriented designed to be converted into various models of the same material, with functions that can accommodate the needs of display clothes, shoes, bags, and accessories that remain fulfilled in each module. Application of modular concept applied with knockdown system, using stalbuis pipe consisting of 3 size that is, 40 cm, 21.2 cm, and 20 cm. To connect a stalbuis pipe using a uno joker joint, a nut and bolt joint, and a deep joint. As a flat cross section using canvas sheeting tarp consisting of 2 sizes that is, 13 cm x 51 cm and 4 cm x 51 cm.